2019
DOI: 10.1111/epi.16290
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of prospective brain development in youth with benign epilepsy with centrotemporal spikes and its relationship to cognition

Abstract: Objective Benign epilepsy with centrotemporal spikes (BECTS) is the most common childhood idiopathic localization‐related epilepsy syndrome. BECTS presents normal routine magnetic resonance imaging (MRI); however, quantitative analytic techniques have captured subtle cortical and subcortical magnetic resonance anomalies. Network science, including graph theory (GT) analyses, facilitates understanding of brain covariance patterns, potentially informing in important ways how this common self‐limiting epilepsy sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…These results indicated that BECTS children have early cognitive impairment, which is roughly the same as previous studies (Vannest et al., 2015; Yan et al., 2017). Some studies have confirmed that the change of brain network is the cause of the onset of epilepsy, and the change of brain network even occurs before the seizure (Garcia‐Ramos et al., 2019). Epilepsy is a connective disease.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results indicated that BECTS children have early cognitive impairment, which is roughly the same as previous studies (Vannest et al., 2015; Yan et al., 2017). Some studies have confirmed that the change of brain network is the cause of the onset of epilepsy, and the change of brain network even occurs before the seizure (Garcia‐Ramos et al., 2019). Epilepsy is a connective disease.…”
Section: Discussionmentioning
confidence: 95%
“…ies have confirmed that the change of brain network is the cause of the onset of epilepsy, and the change of brain network even occurs before the seizure(Garcia-Ramos et al, 2019). Epilepsy is a connective disease.…”
mentioning
confidence: 83%
“…On the whole, the mean cognitive scores were slightly reduced in all groups of patients with CECTS, which coincides with numerous publications. 2426 In the first group (n = 32), 31% of parents (n = 10) reported that their child occasionally had trouble concentrating on a task, finding the correct words, doing one thing at a time, remembering things, making plans or decisions, and these children reacted slowly to things that were being said or done. These manifestations may be owing to seizures, comorbidities including attention deficit hyperactivity disorder (ADHD), or other factors.…”
Section: Resultsmentioning
confidence: 99%
“…Rolandic seizures occur in a period of significant brain maturation. The dysfunction of neuronal network activities such as focal discharges may be associated with neuropsychological problems, including, linguistic, cognitive, and behavioral impairment [28][29][30]122]. The frequent spike discharges in sleep may boost language and attention processing problems [120,[123][124][125].…”
Section: Prognosismentioning
confidence: 99%